Keanekaragaman Burung pada Berbagai Tipe Vegetasi di Resort Aikmel, Taman Nasional Gunung Rinjani, Nusa Tenggara Barat - Anesha Allasselcida; Dinda Tri Agustina; Niskan Walid Masruri; Viny Volcherina Darlis; Lefdi Agung Nugraha; Hanifah Ikhsani (Jurnal Ilmu Ilmu Kehutanan, 2026)
Birds are important components of ecosystems whose diversity is strongly influenced by habitat conditions, vegetation structure, and food availability. This study aimed to analyze bird diversity across different vegetation types in Aikmel Resort, Mount Rinjani National Park, including primary dryland forest, secondary dryland forest, savanna, and post-encroachment areas (PKTI). Bird observations were conducted using the point count method with a 50 m observation radius at 20 sampling points. Analyses included species encounters, diversity index, species richness, dominance, and species similarity among vegetation types. A total of 503 individuals representing 22 species and 16 families were recorded during the study. The PKTI area showed the highest number of individuals (250 individuals; 13 species), whereas the savanna had the lowest (42 individuals; 8 species). Primary dryland forest exhibited the highest diversity index (  = 2,14), likely due to its dense canopy cover and more complex vegetation structure. Secondary dryland forest had the highest species richness index (  = 2,43), while the savanna was dominated by Collocalia linchi. The highest species similarity index was observed between primary and secondary dryland forests (0,35). Differences in vegetation structure and habitat complexity influenced bird composition and diversity across vegetation types. These findings highlight the importance of habitat heterogeneity in supporting bird conservation within Mount Rinjani National Park.